Ulva lactuca Linnaeus Potentially Promotes Reproductive Indices and Depressive-like Behavior of Hypertriglyceridemia Male Wistar Rats (Rattus norvegicus Berkenhout, 1769) - Anggoro Chandra Yulistiyanto; Mayumi Hersasanti; Rahadian Yudo Hartantyo; Laksmindra Fitria; Abdul Razaq Chasani; Mulyati Mulyati (Universitas Gadjah Mada, 2020)
Excessive consumption of fatty foods can lead to hyperlipidemia, which is often coupled with hypertriglyceridemia (HTG), a condition where blood plasma triglyceride (TG) levels elevated beyond normal levels. This condition may disturb physiological functions of the body, such as reproductive functions, and other physiological imbalances leading to chronic stress and depression. Ulva lactuca is a potential natural treatment for HTG, as it contains various nutrients to aid physiological functions. This seaweed also has high levels of Cd, which can increase depression. Therefore, research on the potential benefits of U. lactuca should be followed by an investigation of its health risks. This research aimed to examine the effects of HTG and treatment with U. lactuca on reproduction and depressive-like behavior of male Wistar rats (Rattus norvegicus Berkenhout, 1769). The data collected in this research include body weight, serum TG concentration, gonadosomatic index (GSI), serum testosterone concentration using competitive ELISA, and depressive-like behaviors assessed using the Forced Swim Test (FST) and Open Field Test (OFT). Data were analyzed using One-Way ANOVA followed by DMRT, independent- and paired-samples t-test, and Kruskal-Wallis H test with a significance value of α=0.05. Body weight, serum TG and testosterone concentration, GSI, and depressive-like behaviors were increased by the HTG condition. Ulva lactuca at the1500 mg/kg BW/day did not significantly affect body weight, testosterone concentration, and depressive-like behaviors of HTG rats. Meanwhile, this treatment significantly increased the GSI and depressive-like behaviors of healthy rats. These results suggest that Ulva lactuca treatment not only enhances gonad growth and development but also increases depressive-like behaviors.